If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8 = x + 8 Reorder the terms: 8 + 6x = x + 8 Reorder the terms: 8 + 6x = 8 + x Add '-8' to each side of the equation. 8 + -8 + 6x = 8 + -8 + x Combine like terms: 8 + -8 = 0 0 + 6x = 8 + -8 + x 6x = 8 + -8 + x Combine like terms: 8 + -8 = 0 6x = 0 + x 6x = x Solving 6x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6x + -1x = x + -1x Combine like terms: 6x + -1x = 5x 5x = x + -1x Combine like terms: x + -1x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| 2x+5=3x+7 | | x+2=5x+26 | | 6x-4=44 | | 24y^2-73Y-42= | | m^2+4m-25=0 | | y=x^2-1.5x-3 | | y=x^2-1.5-3 | | 8x-3=4x+7 | | x^3+5x^2+7x+35=0 | | 2x+b=c-b | | 4x^2+17x-15=0 | | 9y+1=3y-5 | | 6x-1=5x+8 | | 9y+6=3y | | x^3-4x^2-32x=0 | | 9x^2-58x+24=0 | | 9x^2+40x+16=0 | | k+1.5=3 | | (5u^2-3u-2)+(u^2-7u+4)= | | 9x^2+18x=0 | | N-8.09=11.3 | | 2r^3+3r^2-20r=0 | | 5((x-9)(x-9))=3 | | 5x-13y=7 | | 5(x^2-18x+81)=30 | | 3r^2+13r=10 | | 3r^2+13=10 | | 9p^2=-21p-6 | | .4y-y=-.2(3y+2) | | (-7q^5-8q^4+6q^3-6q^2)-(-6q^4+2q^3-2q^2)= | | (2x^2)-x-59=0 | | 5x+9=4x+15 |